2011
DOI: 10.1186/1471-2172-12-60
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of in vivo primed transgenic T cells supports allergic lung inflammation and FIZZ1 and Ym1 production in an IL-4Rα and STAT6 dependent manner

Abstract: BackgroundCD4+ T helper type 2 (TH2) cells, their cytokines IL-4, IL-5 and IL-13 and the transcription factor STAT6 are known to regulate various features of asthma including lung inflammation, mucus production and airway hyperreactivity and also drive alternative activation of macrophages (AAM). However, the precise roles played by the IL-4/IL-13 receptors and STAT6 in inducing AAM protein expression and modulating specific features of airway inflammation are still unclear. Since TH2 differentiation and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 69 publications
(134 reference statements)
4
49
0
Order By: Relevance
“…RELMa is expressed by macrophages and pulmonary epithelial cells [2] and also by pulmonary vascular cells during hypoxia [1]. The Th-2 cytokines IL-4 and IL-13 induce RELMa expression via STAT6 and JAK-1 pathways [3,5]. RELMa has the capacity to promote lung cell proliferation, angiogenesis, and inflammation [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…RELMa is expressed by macrophages and pulmonary epithelial cells [2] and also by pulmonary vascular cells during hypoxia [1]. The Th-2 cytokines IL-4 and IL-13 induce RELMa expression via STAT6 and JAK-1 pathways [3,5]. RELMa has the capacity to promote lung cell proliferation, angiogenesis, and inflammation [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of STAT6 signaling caused a significant reduction in Retnla and Chi3L3 mRNA levels in bleomycin-induced lung fibrosis and allergic peritonitis models, respectively [27,28]. Using a murine model of asthma, we found that the number of AAMs recruited to the lungs in mice lacking STAT6 or IL-4Rα was much lower when compared to wild-type (WT) mice [29]. It has also been demonstrated that promoter regions of the Arg1 , Retnla and Chi3L3 genes have consensus STAT6-binding sites [28,30,31].…”
Section: Alternatively Activated Macrophagesmentioning
confidence: 99%
“…The contribution of FIZZ1 to asthma is still unclear. Our studies have shown that IL-4 induces robust induction of FIZZ1 mRNA in macrophages in vitro [25], but FIZZ1 protein expression in these cells was absent in vivo in a mouse model of asthma [29]. …”
Section: Specific Contribution Of Aam Products To Allergic Lung Inflamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that B cells from mice lacking STAT6 failed to produce significant amounts of IgE and IgG1 after infection with the nematode parasites (Raia et al, 2011;Turqueti-Neves et al, 2014). The binding sites of STAT6 have been found in the target regions of a variety of IL-4-mediated genes, including CD23 (Cooper et al, 2012), IL-4R (Jenkins et al, 2013), eotaxin-1 (Waddell et al, 2013), eotaxin-3 (Nakayama et al, 2010), FIZZ1 (Dasgupta et al, 2011), and in Ig germline e (Lu et al, 2007) promoters. Recently, IL-4-driven STAT6 constitutive activation has been found in various diseases, such as allergy (Hong et al, 2014), tumors (Cheah et al, 2014;Creytens et al, in press;Koelsche et al, 2014), and lymphoproliferative disorders (Rawal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%